Strategi Pengajaran Terpadu untuk Meningkatkan Kualitas Pembelajaran Siswa di Yayasan Perintis Pendidik Nusa Melalui Pendekatan Multidisiplin - Aisah, Prity Nur; Ningsih, Diana Fitria; Nurramidhan, Alfath Rizka; Tangdilallo, Aresth Cariv Kila; Widyastuti, Hardiana; Damari, Arfan (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
According to UNESCO, around 258 million children and adolescents worldwide lacked access to education in 2020, most of whom are in developing countries. In Indonesia, while cities like Bogor have good access to education, villages such as Benteng in Bogor Regency still face challenges in educational development, especially in subjects such as English, Mathematics, Social Studies (IPS), and Digitalization. This community service program aims to enhance education quality through interactive learning approaches, including four main programs: ELEVEN (English Learning and Vocabulary ENhancement), Back2Math (Back to Basic Math), Jelajah Duniaku, and DigiKidz. The program employs hands-on training methods, educational games, and game card method to enrich vocabulary, mathematical concepts, social insights, and digital skills. The results show significant improvement in students' academic abilities across all subjects taught. This program also produces learning modules that can be used sustainably by local teachers and communities.